Reduction of body fat and improved lipid profile associated with daily consumption of a Puer tea extract in a hyperlipidemic population: a randomized placebo-controlled trial - Jensen GS (Dove Medical Press, 2016)
Gitte S Jensen,1 Joni L Beaman,1 Yi He,2 Zhixin Guo,2 Henry Sun31NIS Labs, Klamath Falls, OR, USA; 2Modern TCM Research Center, Tasly Academy, Tianjin, People’s Republic of China; 3Tasly Pharmaceuticals Inc, Rockville, MD, USA Objective: The goal for this study was to evaluate the effects of daily consumption of Puer tea extract (PTE) on body weight, body-fat composition, and lipid profile in a non-Asian population in the absence of dietary restrictions.Materials and methods: A randomized, double-blind, placebo-controlled study design was used. A total of 59 overweight or mildly obese subjects were enrolled upon screening to confirm fasting cholesterol level at or above 220 mg/dL (5.7 mmol/dL). After giving informed consent, subjects were randomized to consume PTE (3 g/day) or placebo for 20 weeks. At baseline and at 4-week intervals, blood lipids, C-reactive protein, and fasting blood glucose were evaluated. A dual-energy X-ray absorptiometry scan was performed at baseline and at study exit to evaluate changes to body composition. Appetite and physical and mental energy were scored at each visit using visual analog scales (0–100).Results: Consumption of PTE was associated with statistically significant weight loss when compared to placebo (P<0.05). Fat loss was seen for arms, legs, and the gynoid region (hip/belly), as well as for total fat mass. The fat reduction reached significance on within-group analysis, but did not reach between-group significance. Consumption of PTE was associated with improvements to lipid profile, including a mild reduction in cholesterol and the cholesterol:high-density lipoprotein ratio after only 4 weeks, as well as a reduction in triglycerides and very small-density lipoproteins, where average blood levels reached normal range at 8 weeks and remained within normal range for the duration of the study (P<0.08). No significant changes between the PTE group and the placebo group were seen for fasting glucose or C-reactive protein. A transient reduction in appetite was seen in the PTE group when compared to placebo (P<0.1).Conclusion: The results from this clinical study showed that the daily consumption of PTE was associated with significant weight loss, reduced body mass index, and an improved lipid profile.Keywords: body mass index, DEXA, cholesterol, triglycerides